The barriers to clinical coding in general practice a literature review. - De Lusignan, S. (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
Clinical coding is variable in UK general practice. The reasons for this remain undefined. This review explains why there are no readily available alternatives to recording structured clinical data and reviews the barriers to recording structured clinical data. Methods used included a literature review of bibliographic databases, university health informatics departments, and national and international medical informatics associations. The results show that the current state of development of computers and data processing means there is no practical alternative to coding data. The identified barriers to clinical coding are: the limitations of the coding systems and terminologies and the skill gap in their use; recording structured data in the consultation takes time and is distracting; the level of motivation of primary care professionals; and the priority within the organization. A taxonomy is proposed to describe the barriers to clinical coding. This can be used to identify barriers to coding and facilitate the development of strategies to overcome them.